Population biology of shrimp Artemesia longinaris (Crustacea: Decapoda: Penaeidae) from the southern coast of Brazil - da Costa, Rogerio Gaetano [UNESP]; Branco, Joaquim Olinto; Machado, Irece Farina; Campos, Bruno Ribeiro; Avila, Marcelo Gentil (Cambridge University Press, 2010)
Size at morphological sexual maturity, sex-ratio, and the seasonal variation in abundance of the shrimp Artemesia longinaris Bate, 1888 were assessed off Pinheira Beach, Palhoca, Santa Catarina southern Brazil Shrimp were collected monthly from November 2003 through to October 2004, in two areas that are customarily used by local traditional fishermen (27 degrees 52'-27 degrees 51'S and 48 degrees 33' - 48 degrees 29' W) of the total of 1099 specimens measured, 23 9396 were males and 76 0796 females. Mean size at first maturity (LM(50)) was estimated as 56 38 mm total length (TL) for males, and 70 34 111111 TL for females. Females were significantly larger than males. Abundance of juveniles varied seasonally. A high predominance of juveniles in the areas sampled occurred in winter for both sexes, and in spring for females In the summer and autumn, we observed a decrease in juveniles in both areas, mainly, area 11 We suggest that the differential migration pattern of sexes during the reproductive cycle was the principal reason for the larger catch of females. The classical paradigm of continuous reproduction at lower latitude, with increased seasonality of the breeding period at higher latitudes, seems to apply to tins species
Keywords: maturity; recruitment; distribution; sex ratio; shrimp fishery; Brazil